Microclimate Condition in the Natural Ventilated Greenhouse - Vita Ayu Kusuma Dewi; Budi Indra Setiawan; Roh Santoso Budi Waspodo; Liyantono Liyantono (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2020)
A Greenhouse has a different microclimate compared to the outside field. Climate parameters such as solar radiation and air temperature are important parameters that affect plant growth and productivity. This research aims to understand the relation of climate factors in the inside and outside Greenhouse, the effect of microclimate on evapotranspiration and to predict the amount og evapotranspiration inside the Greenhouse. Microclimate analysis was held in two stages, the firststage was from February 5 to March 21, 2018 and the second stage from March 19 to April 29, 2019 at the Department of Civil and Environmental Engineering, IPB University. Primary data was measured by the Decagon sensor. Solar radiation was collected using the Decagon PYR Pyranometer sensor and air temperature using the Decagon VP-4 sensor. Based on the result, the daily air temperature inside the Greenhouse was higher than that of the outside. The inside solar radiation was lower than that of outside the Greenhouse. The relative humidity fluctuated, and the air pressure was higher inside the Greenhouse. Evapotranspiration inside the Greenhouse was lower than outside and solar radiation was the most determining factor of evapotranspiration.